Pendidikan Islam Berbasis Kasih Sayang - Ma’ruf Ma’ruf (Raheema, 2019)
It is no doubt that the concept of Islamic Education has comprehend theories, even there are always new perspectives about its values. Thus, this writing is conducted to elaborate the concept of Islamic Education in the globalization era. The term of affection (Kasih Sayang) has a functional meaning in Islamic theory, Islam Rahmatan Lil-‘Alamin that is originated from QS. al-Anbiya verse 107 with multiperspective mufassir. The verse on al-Maraghi is translated that Muhammad as a prophet with a holy book which is not only as a guidance, but also a rahmah (affection). Furthermore, the awareness of education as a media of universal awareness should be understood by every educators. Islamic Education, moreover, should present the true values of education, that is “Affection”.